Discussion - Of Mr. Baker's Paper on Improvements in the Mechanical Charging of the Modern Blast-Furnace (see p. 553) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
Mr. John J. Porter, Chicago Ill. (communication to the Secretary†):—Mr. Baker's account of his experiences with stock-distribution has been particularly interesting to me, as it